Implementasi Program Bantuan Sosial Tunai Dalam Upaya Mengatasi Masalah Ekonomi Akibat Pandemi Covid 19 Di Nagori Silou Huluan Kecamatan Raya Kabupaten Simalungun - Cynthya Lawrency Saragih; Beby Masitho Batubara; Evi Yunita Kurniaty (Universitas Medan Area, 2023)
During the COVID-19 pandemic that occurred in Indonesia, the economy declined so that new people who could not afford it emerged. This is without exception in Nagori Silou Huluan, where the people who work as farmers have decreased their income. Especially when the Covid-19 virus has just entered, the government has implemented a lockdown. As a result, the delivery of goods out of the region cannot. Poor/poor people are getting poorer. This study aims to find out how the implementation of the cash social assistance program for underprivileged communities affected by the Covid-19 virus outbreak in Nagori Silou Huluan and to find out what are the obstacles in implementing the BST program in Nagori/Silou Huluan Village. This study uses a qualitative research method with a descriptive type. This study uses the theory of Van Meter and Van Horn there are six indicators, namely the size and objectives of policies, resources, communication between organizations and strengthening activities, characteristics of implementing agents, attitudes of implementers and the economic, social and political environment. Data collection techniques were carried out by means of observation, interviews, and documentation. The results of the study indicate that the implementation of the cash social assistance program still cannot be said to be running effectively in the distribution of assistance to help the poor/poor. It can be seen from the data collection process that the village government was not carried out, as a result there were still poor/poor people who did not get BST. Also, there is no fixed schedule for disbursing cash social assistance funds, resulting in the disbursement process not running properly. Whereas cash social assistance is used for basic needs.